Motor controller design for a 2-DOF robotic pan-tilt platform module - Yu, Quanfang (Nanyang Technological University, 2023)
This project aims to develop a standalone motion control module for a building inspection robot. The purpose of this motor controddller is to control a 2-DOF pan-tilt-perception camera platform. The entire building inspection robot consists of three parts: the bottom part is the wheels, the middle part is composed of an external battery, a camera, and internal circuitry that rely on the motor to achieve a 180-degree rotation of the camera from left to right to capture wall information, and the top part consists of the camera and the motor, which rely on the motor to drive the camera up and down with a 180-degree rotation to capture floor and ceiling information. Therefore, the motor controller must be able to generate and coordinate the motion profile of the two DC servo motors and accurately accept encoder readings. The controller must also be able to communicate with the embedded MCU and interface with the main robot controller. The entire pan-tilt module will be a DC battery-powered system. The servo motor in this project consists of a potentiometer (RDC503013A), a DC brushed motor (JGA1024-N20), a driver (L9110s), and a single chip microcomputer (STC15W408AS)to form a closed-loop feedback system. It can rotate from 0 to 333 degrees and is connected to the computer through a USB-to-serial converter (CH340T). The system can receive commands through the serial port communication and accurately rotate to the specified position. The microcontroller continuously performs ADC detection using a timer and adjusts the rotation position based on the feedback from the potentiometer's ADC data and the difference between the received command and the actual position, making the rotation more accurate.